2021
DOI: 10.15244/pjoes/131056
|View full text |Cite
|
Sign up to set email alerts
|

A Long-Term Analysis of Spatiotemporal Change and Driving Factors on Poyang Lake during 1987-2019

Abstract: As the largest freshwater Lake in China, Poyang Lake plays an important role in regulating the water level of Yangtze River and maintaining the ecological balance of surrounding areas. Therefore, this study utilizes Google Earth Engine (GEE) geospatial technology to acquire 124 remotely sensed images to explore the spatial and temporal changes of the four seasons of Poyang Lake from 1987 to 2019. The official statistics from relevant cities are used to quantitatively reveal the main driving factors of water bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Under the technological advantage, enterprises can utilize digital technology to develop products and drive their participation in emergency response, such as the emergency material supply chain big data management platform of China JD Logistics and the intelligent epidemic prevention black technology matrix created by SAIC GM Wuling. In order to understand the main driving factors affecting the changes in the water body of Poyang Lake, Zhu et al ( 41 ) analyzed the spatiotemporal changes of the four seasons of Poyang Lake through 124 remote sensing images, and found that both human and natural factors are the main driving factors affecting the changes in the water body of the lake. It can be seen that the results of the study are similar to those of experts such as Zhu et al ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Under the technological advantage, enterprises can utilize digital technology to develop products and drive their participation in emergency response, such as the emergency material supply chain big data management platform of China JD Logistics and the intelligent epidemic prevention black technology matrix created by SAIC GM Wuling. In order to understand the main driving factors affecting the changes in the water body of Poyang Lake, Zhu et al ( 41 ) analyzed the spatiotemporal changes of the four seasons of Poyang Lake through 124 remote sensing images, and found that both human and natural factors are the main driving factors affecting the changes in the water body of the lake. It can be seen that the results of the study are similar to those of experts such as Zhu et al ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…In order to understand the main driving factors affecting the changes in the water body of Poyang Lake, Zhu et al ( 41 ) analyzed the spatiotemporal changes of the four seasons of Poyang Lake through 124 remote sensing images, and found that both human and natural factors are the main driving factors affecting the changes in the water body of the lake. It can be seen that the results of the study are similar to those of experts such as Zhu et al ( 41 ). In addition, the western region of China has the highest level of PHE, with the strongest seasonal intensity index from 2013 to August 2022.…”
Section: Discussionmentioning
confidence: 99%
“…Correlation analysis involves the breakdown of the association among two or more variables, usually to analyze whether the trends in two or more sets of data are consistent [25][26][27]. SPSS25 software was used to explore which factors were associated with the NPP value.…”
Section: Correlation Analysismentioning
confidence: 99%
“…Spatial correlation analysis was carried out between NPP and land cover to calculate correlation coefficients and clarify their association. The Pearson correlation coefficient was used to measure whether the two datasets lie on top of a line and to measure the linear relationship between the fixed distance variables [41][42][43]. Sig is an abbreviation for statistical significance [44].…”
Section: Spatial Correlation Analysismentioning
confidence: 99%